Chronic kidney disease, proteinuria, and mortality risk in patients with Parkinson’s disease: a 12-year longitudinal study - Baik, Kyoungwon; Kang, Minwoong; Park, Yu Jeong; Chung, Su Jin; Oh, Kyungmi; Kang, Sung Hoon; Koh, Seong-Beom (Frontiers in Aging Neuroscience, 2025)
BackgroundVarious comorbidities contribute to mortality in patients with Parkinson’s disease (PD). Although growing evidence demonstrates that chronic kidney disease (CKD) increases the risk of developing PD, the effect of CKD on all-cause mortality remains unclear.MethodsWe enrolled 59,293 patients aged ≥40 years with de novo PD between 2009 and 2015, using de-identified data from the Korean National Health Insurance Service. Cox proportional hazards regression analysis using the presence of CKD or proteinuria as a predictor was performed to investigate the association between CKD, proteinuria, and mortality. For sensitivity analysis, the degree of eGFR or proteinuria were used as predictors in place of CKD/proteinuria.ResultsParkinson’s disease patients with CKD (hazard ratio [HR] = 1.240, 95% confidence interval [CI] 1.190–1.283) and proteinuria (HR = 1.543, 95% CI 1.457–1.634) had a higher risk of mortality, even after controlling for confounding factors. The degree of kidney dysfunction (p < 0.001) and proteinuria (p < 0.001) were associated with an increased HR for mortality. Furthermore, female patients with CKD were more vulnerable to mortality than male patients (p for sex × CKD < 0.001); however, there was no sex-specific vulnerability of proteinuria to mortality (p for sex × proteinuria = 0.603).ConclusionChronic kidney disease and proteinuria were associated with a higher all-cause mortality in patients with PD in a dose-dependent manner. Furthermore, these results highlight that strategies for controlling kidney function are necessary to reduce mortality in patients with PD.